Non Political Grassroots Leadership and Sustainable Development in Nigeria: An Analysis of Challenges and Policy Proposals - Maduabum C.; Akhakpe Ighodalo (European Scientific Journal, ESJ, 2018)
The paper argued that Nigeria is inundated with rich human and material resources begging to be harvested by purposeful, creative and innovative leadership. Development that is based on the cultural values of the people and takes a bottom-top approach, holds the key to unlocking the development potentials and at the same time resolve the quagmire the country has found itself since flag independence in 1960. Rather than seek to replicate Western prototype of development, empowering the people through Community Based Organizations (CBOs) to make the right choices and change their situation in such a way that each stage of their lives is increasing better than the proceeding one, is the basis of sustainable development. This can only be realized however, if the right caliber of leadership is in charge of affairs and able to harness and utilize available resources for the growth and development of the grassroots. With the use of the Basic Need Theory (BNT), the paper analyzed issues of grassroots non-political leadership and the role it can play in sustainable development. Drawing experiences from developed and developing countries in the globalize era, it concluded that grassroots leadership cannot successfully address challenges of sustainable development, unless, among other things, it embraces global best practices cultivated and harvested from within Nigeria in the globalize era, promote democracy within CBOs, encourage popular participation, good governance at the grassroots, and financial independence and transparency in the usage or management of financial resources.